2013
DOI: 10.1111/jth.12276
|View full text |Cite
|
Sign up to set email alerts
|

An interactive mutation database for human coagulation factor IX provides novel insights into the phenotypes and genetics of hemophilia B

Abstract: lation factor IX provides novel insights into the phenotypes and genetics of hemophilia B. J Thromb Haemost 2013; 11: 1329-40.Summary. Background: Factor IX (FIX) is important in the coagulation cascade, being activated to FIXa on cleavage. Defects in the human F9 gene frequently lead to hemophilia B. Objective: To assess 1113 unique F9 mutations corresponding to 3721 patient entries in a new and up-to-date interactive web database alongside the FIXa protein structure. Methods: The mutations database was built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
234
0
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(266 citation statements)
references
References 46 publications
17
234
0
15
Order By: Relevance
“…Point mutations (single-nucleotide substitutions) were the most common gene defects. This result is consistent with another study, which reported that point mutations are present in approximately 73% of patients with HB [8]. CG transitions can cause missense or nonsense mutations, depending on the codon involved and the types of transition (C-to-T or G-to-A).…”
supporting
confidence: 94%
“…Point mutations (single-nucleotide substitutions) were the most common gene defects. This result is consistent with another study, which reported that point mutations are present in approximately 73% of patients with HB [8]. CG transitions can cause missense or nonsense mutations, depending on the codon involved and the types of transition (C-to-T or G-to-A).…”
supporting
confidence: 94%
“…These are mostly point mutations (73.0%), missense in the majority of the cases (74.4%). 3 Simultaneous short insertions and deletions (indels) constitute about 1.5% of the mutations, whereas gross gene deletions account for about 16.3% of the cases. Another group of mutations that occur in the promoter region of the FIX gene result in HB Leyden.…”
Section: Introductionmentioning
confidence: 99%
“…Although in hemophilia A about 80% of the patients exhibit null mutations with no endogenous FVIII protein synthesis, hemophilia B show only about 20% to 30% null mutations. 66,67 Hemophilia B especially is much more commonly caused by missense mutations, which might be associated with some small amounts of endogenous plasma FIX protein. In their 2010 study, Santagostino and coworkers showed that the type of mutation was the only significant parameter influencing the phenotype.…”
Section: Prophylaxis In Hemophilia Bmentioning
confidence: 99%